2015
DOI: 10.1590/1516-4446-2014-1414
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cortisol, norepinephrine, and epinephrine levels with war-induced posttraumatic stress disorder in fathers and their offspring

Abstract: Objective: To compare afternoon serum/plasma levels of hormones in four groups: (A) veterans with posttraumatic stress disorder (PTSD), (B) offspring of PTSD veterans, (C) veterans without PTSD, and (D) offspring of non-PTSD veterans. Methods: Evaluation consisted of a semi-structured interview for axis I and II diagnoses, followed by measurement of afternoon serum cortisol and plasma epinephrine and norepinephrine by ELISA (Diametra) and LND (LDN Labor Diagnostika Nord GmbH & Co. KG) respectively. Data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Observations in offspring whose parents were exposed to other traumatic experiences accorded with these findings. For example, lower cortisol levels were observed in the adult offspring of combat veterans with PTSD compared to offspring of combat veterans without PTSD.…”
Section: The Introduction Of Biological Research Into the Study Of Inmentioning
confidence: 97%
“…Observations in offspring whose parents were exposed to other traumatic experiences accorded with these findings. For example, lower cortisol levels were observed in the adult offspring of combat veterans with PTSD compared to offspring of combat veterans without PTSD.…”
Section: The Introduction Of Biological Research Into the Study Of Inmentioning
confidence: 97%
“…Traumatic brain injury, a relatively common injury experienced by service members across both deployed and non-deployed combat environments, may even constitute an occupational hazard [24]. In groups chosen for similarity in relation to demographic characteristics and affective profiles, war experience and traumatization, and psychiatric and medical conditions other than PTSD, the altered levels of cortisol in offsprings of veterans did not follow any systematic pattern [25]. It was found that depressiveness and anxiety associated with combat war zone deployment present powerful predictors of PTSD symptoms, c-reactive protein and hair cortisol which were shown to be correlated both with each other and with depressiveness and PTSD symptoms [26].…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol also regulates lipolysis and proteolysis for energy and biosynthesis, and has been implicated in memory processes and wound healing . Cortisol is an important biomarker for posttraumatic stress disorder (PTSD), Cushing's syndrome, Addison's disease, and other conditions. Hence, an implantable biosensor capable of real time monitoring of cortisol concentration would be of significant value for diagnosis and treatment of these disorders, as well as general scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…In Cushing's syndrome, high concentrations of cortisol can have several consequences, including muscle weakness, an irregular fat distribution, hypertension, dermatological issues, and higher mortality rates . Other conditions that may be associated with abnormal cortisol levels and production include obesity, memory consolidation, chronic and acute stress, posttraumatic stress disorder, major depressive disorder, bipolar disorder, and schizophrenia …”
Section: Introductionmentioning
confidence: 99%